KAJIAN LITERATUR: PENGEMBANGAN INSTRUMEN DALAMBIMBINGAN DAN KONSELING - Tisaul Nabila Isvianti; Sazkia Septa Febriyanti; Kayla Ramadhani; Fitria Ramadhani; Minarsi Minarsi; Yola Eka Putri (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to find out what makes a good research tool by looking at other studies that have already been done. This studys main focus is the continued use of instruments that do not satisfy the required validity and dependability standards in educational research, therefore generating incorrect data and jeopardizing the validity of research findings. A literature review strategy was used for this study whereby twenty-five regionally and globally recognized publications connected to research instrument quality were examined. The results indicate that a good research tool has to meet a number of fundamental requirements, including content validity, construct validity, criterion validity, dependability, and a low level of measurement error. Furthermore, the data show that calibrating tools by means of item analysis is a vital stage in guaranteeing the accuracy and dependability of measurement instruments. The study finds that the quality of a research tool is a crucial factor in producing reliable and legitimate research data.